2016
DOI: 10.1016/j.actamat.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Alpha – omega and omega – alpha phase transformations in zirconium under hydrostatic pressure: A 3D mesoscale study

Abstract: a b s t r a c tA three dimensional (3D) elastoplastic phase-field model is developed for modeling the hydrostatic pressure-induced alpha e omega phase transformation and the reverse phase transformation, i.e. omega e alpha, in zirconium (Zr). Plastic deformation and strain hardening of the material are also considered in the model. The microstructure evolution during both phase transformations is studied. The transformation start pressures at different temperatures are predicted and are plotted as a phase diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The displacive transformation from α-Zr (or Ti) to ω-Zr (or Ti) under hydrostatic pressure has been shown to be controlled by time, pressure and impurities [27,28,81,83,85], so is not a simple diffusionless martensitic transformation. This behavior is similar to paraequilibrium transformations in which the larger atoms in the substitutional sites move in a military manner (without diffusion) whereas the interstitial atoms diffuse more easily and can partition between the phases [84,86,87].…”
Section: The Formation Mechanisms Of H-zro Suboxidementioning
confidence: 99%
See 1 more Smart Citation
“…The displacive transformation from α-Zr (or Ti) to ω-Zr (or Ti) under hydrostatic pressure has been shown to be controlled by time, pressure and impurities [27,28,81,83,85], so is not a simple diffusionless martensitic transformation. This behavior is similar to paraequilibrium transformations in which the larger atoms in the substitutional sites move in a military manner (without diffusion) whereas the interstitial atoms diffuse more easily and can partition between the phases [84,86,87].…”
Section: The Formation Mechanisms Of H-zro Suboxidementioning
confidence: 99%
“…However, the mechanism by which the h-ZrO forms has not yet been explored. Extensive research has been undertaken to identify the mechanisms controlling the α to ω phase transformation in Ti and Zr [26][27][28] showing it to be displacive martensitic in nature [29,30]. Similar transformations have been observed in steels [31,32], shape memory alloys [33] and ceramics [34], but this kind of transformation has not been considered to play a role in the aqueous corrosion of alloys.…”
Section: Introductionmentioning
confidence: 98%
“…The to ! phase transformation in Zr and Ti under hydrostatic pressure has been regarded as a displacive transformation (Yeddu et al, 2016;Hennig et al, 2005;Trinkle et al, 2003;Rabinkin et al, 1981). The OR between the phase and the !…”
Section: Figurementioning
confidence: 99%
“…External support for the kinked phase boundary comes from reversion studies from ω to α, which have shown that the temperature required to stimulate reversion to the ambient phase must be in excess of 470 K [15]. Further theoretical support for the kinked phase boundary has also recently been provided by Yeddu et al [46], whose report shows clearly a kinked phase boundary from simulational results. From our results, we propose that shear softening and the phase boundary kink are coupled in nature.…”
Section: B Phase Boundary Kink and Shear Softeningmentioning
confidence: 77%